IDENTIFIKASI KEBUTUHAN KOMPETENSI SUMBER DAYA MANUSIA INDUSTRI PERHOTELAN KABUPATEN BANTUL - Prihatno, Prihatno (JURNAL MEDIA WISATA: Wahana Informasi Pariwisata, 2017)
At present the accommodation services business has become a service industry and is a labor-intensive business means Human Resources support becomes the mainstay of business success. Improved customer service requires a more professional Human Resource capability. As a standard measure that professionals in the field of tourism including hospitality staff and restaurants is possessed a certificate of competence recognized by the National Agency for Professional Certification. In Bantul Regency this accommodation business is growing very rapidly following the development of tourism. The number of existing hotels and inns has reached 95 units for the class with the number of medium rooms, but if recorded all including lodging in the location of objects that only has one room, the number reaches 261 pieces and may continue to grow in the future With the emergence of objects of new attractions. Bantul regency government tries to formulate its development strategy by conducting study of identification of human resource competency requirement for hotel industry in order to give space for the growth and development of hospitality industry in Bantul regency in the future. This study was conducted by taking 30 samples from the workforce and the guest response from the type of accommodation in the form of hotels totaling 5 pieces, the only business mentioning the lodgings amounted to 8 pieces, inn 9 pieces, cabin 6 pieces and each 1 fruit is Inn and Guest House. The data collected by questionnaire and documentation is then processed using Spencer & spencer competency analysis, especially non technical competency or soft competency to determine the level of incompetent to very competent while also ranking the competency level required in the hotel industry. From the research results obtained data real needs of hotel industry competence which then rearranged and selected based on priority scale likert between 1-4. By using competency guideline in Indonesia from work competency standard especially hotel and restaurant area mapped to get requirement of human resource competence for Hotel Industry in Bantul Regency. Keyword: Soft Competency, Hard Competency dan Kompetensi SDM Hotel